If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + 5g = 4g Solving 4 + 5g = 4g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-4g' to each side of the equation. 4 + 5g + -4g = 4g + -4g Combine like terms: 5g + -4g = 1g 4 + 1g = 4g + -4g Combine like terms: 4g + -4g = 0 4 + 1g = 0 Add '-4' to each side of the equation. 4 + -4 + 1g = 0 + -4 Combine like terms: 4 + -4 = 0 0 + 1g = 0 + -4 1g = 0 + -4 Combine like terms: 0 + -4 = -4 1g = -4 Divide each side by '1'. g = -4 Simplifying g = -4
| 40x+8(1.5x)=962 | | 3+2a+4=9-2a | | 2a+14=9 | | 20b-50=14+4b | | n^2-15n+16=0 | | F(x)=x^3-9x^2+24x-23 | | -36-8x=-2(4x-6)-6x | | 24x^2=300 | | 30-7n=9-4n | | d^2-4d+5=0 | | -9+9x+x= | | 30.14+(5p+17)=180 | | 72=-15m-3 | | 12345698+x=100 | | 3(n-2)-n=-12 | | 6x-8x+24=7x+42 | | 10h-5h=20 | | 180-(7p-31)= | | 7j-5j=12 | | 7j-5j=2 | | 1+9x+x+11-9+7x= | | -5(1-7p)-6=-38+8p | | r(a^2-4a+6)-(2a^2-a-7)= | | 20g-19g=3 | | 4p+(p+17)+n=180 | | X-(-24)=-3 | | 10(x+3)=5(x+11) | | 16*7=4*x | | 6+2r-4r=6t | | -3x+7=-4x+1 | | 3s-2s=18 | | 4+2p=6-20 |